Terrorist organizations and the permissibility of the blood of Gentiles (Islamic Sciences Journal, 2024)
ABSTRACT   There is no doubt that terrorism in all its names constitutes a danger to the entire nation and that it threatens the security of safe societies and hinders the progress of progress. The use of terrorism and intimidation makes it a reason to achieve what the user of this term aspires to, alone or with a group supported by a political or partisan entity, in order to obtain Worldly interests in the most horrific ways of terrorism.
Keywords: Organizations, terrorist, permissibility, blood, Gentiles